Large diaphragmatic defect: are skeletal deformities preventable? - Kuklová, P; Zemková, D; Kyncl, M; Pycha, K; Straňák, Z; Melichar, J; Šnajdauf, J; Rygl, M (Pediatric surgery international, 2011)
PURPOSE: The aim of study was to compare growth, nutritional status and incidence of chest wall deformities and scoliosis in survivors of large congenital diaphragmatic hernia (CDH) defect (Gore-Tex patch reconstruction) with survivors with smaller defects and primary reconstruction. MATERIALS AND METHODS: An anthropometric study of 53 children who underwent CDH repair in neonatal period was carried out. Weight, height, and skin-fold thickness were measured, scoliosis and chest wall deformity were evaluated. Body mass index (BMI) and thoracic index (TI) were calculated using standard rules. The measured data were compared with national population standard with the use of standard deviation score (SDS). According to the type of diaphragmatic reconstruction, the patients were divided into two groups [Gore-Tex patch (10) versus primary repair (43)]. Student t test and Fisher exact tests were used for statistical analysis. RESULTS: Pectus excavatum was found in 25 (47%) patients, poor posture in 33% and significant scoliosis in 5%. Compared with the population norm, CDH children had a significantly lower body height SDS (mean -0.39, p < 0.05), weight SDS (mean -0.75, p < 0.001), BMI (mean SDS -0.68, p < 0.001) and lower TI (mean SDS -0.62, p < 0.01). Gore-Tex versus primary repair group significantly differed in incidence of pectus excavatum and BMI (PE: p = 0.027, BMI SDS: p = 0.016). A majority of anthropometric parameters (weight, height, thoracic index, and thorax circumference) and incidence of scoliosis and poor posture in children after Gore-Tex patch reconstruction did not significantly differ from children after primary repair. CONCLUSION: The differences in some anthropometric parameters (weight, BMI, and TI) and in the skeletal deformity suggest that the CDH not only disturbs normal lung growth, but also seems to have implications on some other aspects of somatic development. Whether these changes could be related to the type of diaphragmatic reconstruction or rather to the size of the defect remains uncertain.
Keywords: Polytetrafluoroethylene; retrospektivní studie; Hernia, Diaphragmatic; Child; Surgical Mesh; incidence; skolióza; Humans; lidé; vrozená brániční kýla; Retrospective Studies; Scoliosis; Czech Republic; zákroky plastické chirurgie; Biocompatible Materials; Hernias, Diaphragmatic, Congenital; Female; Male; Radiography, Thoracic; prognóza; Prognosis; Body Mass Index; hrudník vpáčený; mužské pohlaví; Funnel Chest; polytetrafluoroethylen; chirurgické síťky; ženské pohlaví; index tělesné hmotnosti; Plastic Surgery Procedures; biokompatibilní materiály; dítě; Česká republika; Incidence; brániční hernie; rentgendiagnostika hrudníku